2009
DOI: 10.1016/j.inhe.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of men in Nigeria to vasectomy

Abstract: The objective of this study was to assess the attitude of men in Nigeria towards vasectomy as a method of family planning. This was a cross-sectional study, using self-administered pre-tested questionnaires containing mainly close-ended questions. The questionnaires were given to 146 randomly selected men. The responses were analyzed with descriptive statistics. Ten (6.8%) may accept vasectomy with the knowledge they have while 130 (89.0%) will not. Eighty-eight (67.7%) believe sterilization procedures should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 2 publications
1
26
0
1
Order By: Relevance
“…Other studies conducted in Africa (Ghana and Nigeria) have also reported that vasectomy is associated with castration and the fact that it negatively affects men's sexual function (Adongo et al, 2014;Ezegwui & Enwereji, 2009). Furthermore, even in developed countries like the United States, there are men who continue to associate vasectomy with a decrease in libido, sexual potency, and virility (Amor et al, 2008).…”
Section: Beliefs About Vasectomymentioning
confidence: 96%
“…Other studies conducted in Africa (Ghana and Nigeria) have also reported that vasectomy is associated with castration and the fact that it negatively affects men's sexual function (Adongo et al, 2014;Ezegwui & Enwereji, 2009). Furthermore, even in developed countries like the United States, there are men who continue to associate vasectomy with a decrease in libido, sexual potency, and virility (Amor et al, 2008).…”
Section: Beliefs About Vasectomymentioning
confidence: 96%
“…The use of the two male-oriented contraceptive methods, the condom and vasectomy is low compared to the use of other methods, but it is slowly increasing in some countries (Ezegwui and Enwereji, 2009). In most countries, traditional methods that require male cooperation, the withdrawal and abstinence methods are also less utilised.…”
Section: Introductionmentioning
confidence: 99%
“…According to Odu et al (2006), Nigerian men still have poor knowledge and attitude towards family planning despite global move to increase the involvement of men in reproductive health matters. A concerted effort is therefore needed to enhance men's knowledge and increase their involvement in reproductive health (Ezegwui and Enwereji, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge and attitude towards vasectomy have been reported to have significant influence on its uptake among men. For example, a study conducted by Ezegwui and Enwereji (2009) reported that only 6.8% of men may accept vasectomy with the knowledge they currently have while 89% will not. This finding was also linked to the fact that majority of the men believed that sterilization should be left for women only.…”
Section: Introductionmentioning
confidence: 99%